Assessing the Accuracy of Dermoscopy for Scabies Diagnosis in Dark African Skin - Enechukwu, Nkechi Anne; Akuakolam, Ikenna; Aghanya, Iloduba N; Anaje, Chetanna C; Ezejiofor, Ogochukwu I; Errichetti, Enzo (Dermatology Practical & Conceptual, 2025)
Introduction: Scabies, a parasitic infestation caused by Sarcoptes scabiei var hominis affects individuals of diverse skin types. While definitive diagnosis involves identifying adult mites, eggs, or scybala from the microscopy of scrapings obtained from representative sites; it is invasive, time-consuming and not feasible in very young or non-cooperating patients. Dermoscopy is an evolving non-invasive procedure useful in dermatological diagnosis. The handheld dermatoscope is portable and valuable for epidemics and in-vivo use. There is sparse data on the diagnostic accuracy of dermoscopy against microscopy in darker skin phototypes, a demographic for which dermoscopy have been understudied.Objective: This study aimed to compare the diagnostic accuracy of dermoscopy with microscopy in dark skin.Methods: Consecutive patients attending the dermatology clinic at Nnamdi Azikiwe University Teaching Hospital, Nigeria with clinical suspicion of scabies underwent dermoscopic and microscopic examination. Definitive diagnosis was retrospective, and a comparative assessment between dermoscopy and microscopy was conducted.Results: Dermoscopic and microscopic evidence was observed in 48.3% and 46.7% respectively. While the serpiginous tract had a sensitivity and specificity of 75.9% and 80.6% respectively, delta sign was 75% and 55.4% respectively. Both dermoscopy and microscopy demonstrated a sensitivity and specificity of 75% and 55.4% respectively. The delta glider sign was seen in 4 participants.Conclusion: Dermoscopy is particularly effective in identifying the serpiginous tract of scabies on dark skin, although it is less effective for detecting the delta sign. Non-specific dermoscopic features may frequently be seen. Future studies should modify criteria for darker skin to enhance clinical accuracy.